As encarnações da violência caracterizada com totalitária em Der Fuchs war damais schon der Jäger, Herztier e Heute wär ich mir lieber nicht begegnet - Samia Tavares de Souza (2023)
In this thesis, we aim to study the representations of the violence present in three novels written by the author Her ta Müller, Der Fuchs war damals schon der Jäger, Herztier and Heute wär ich mir lieber nicht begegnet, especially that characterized as being totalitarian. For this purpose, we will, in addition to making an individual analysis of each one of the novels, also make a comparative study of them in order to show the relations they establish between each other in terms of their similarities and differences. In the same way, we will also address some of the more general aspects of Herta Müller’s aesthetic, since they are equally important for the comprehension of her writing and are also an integral part of the novels that make up our corpus. On the same vein, since these three Herta Müllers novels have their focus on Romanian totalitarianism during the period in which it had the figure of Nicolae Ceauşescu as a ruler, we will also address it in our thesis, especially in relation to the acts of the Romanian secret police, having as our base the critical work of many authors such as Dennis Deletant (1999, 2006, 2006a) Vladmir Tismaneanu (2003), Katherine Verdery (2014), and Hannah Arendt (2009), among others. Beyond that, we will also base the writing of our thesis on many critical works of other theorists that are dedicated to Müllers oeuvre, such as Nobert Otto Eke (2002, 2013, 2016, 2017), Paola Bozzi (2005,2013,2017), Brigid Haines (2011, 2013), and Lyn Marven (2005, 2011, 2013, 2013a), among many others, and also on other works from Herta Müller herself, such as, for example, her essays, interviews, and speeches, that we take as a counterpoint to discuss many elements of her novels, since Müller (2009, p. 21) indicates her works as being autoficcional.